2022
DOI: 10.1021/acs.molpharmaceut.2c00378
|View full text |Cite
|
Sign up to set email alerts
|

Stable Recombinant Invasion Plasmid Antigen C (IpaC)-Based Single Dose Nanovaccine for Shigellosis

Abstract: Shigellosis, caused by the bacteria Shigella, is the leading cause of bacterial diarrhea and the second leading cause of diarrheal death among children under the age of five. Unfortunately, Shigella strains have acquired resistance to antibiotics, and a commercial vaccine is yet to be available. We have previously demonstrated that Shigella dysenteriae serotype 1 (Sd1)-based recombinant, stabilized, "invasion plasmid antigen C" (IpaC; 42 kDa) protein can induce robust immune responses in BALB/c mice against a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…[3] Nonetheless, by 6 months, the binding antibody titers decreased to prebooster magnitude, and additional boosters were necessary to confer robust protection. [3] While there are a few reports on the development of single-shot nanovaccines, [35][36][37] an antigen-agnostic approach is necessary for a rapidly employable vaccine platform to combat emerging infectious diseases. Therefore, the present study reports the development of a new vaccine platform strategy that could elicit potent, broad, and durable humoral responses without the need for booster shots.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Nonetheless, by 6 months, the binding antibody titers decreased to prebooster magnitude, and additional boosters were necessary to confer robust protection. [3] While there are a few reports on the development of single-shot nanovaccines, [35][36][37] an antigen-agnostic approach is necessary for a rapidly employable vaccine platform to combat emerging infectious diseases. Therefore, the present study reports the development of a new vaccine platform strategy that could elicit potent, broad, and durable humoral responses without the need for booster shots.…”
Section: Discussionmentioning
confidence: 99%
“…The biocompatible and biodegradable poly (lactide- co -glycolide) or PLGA is one of the most widely explored safe (FDA approved for a few drug delivery applications) [ 37 ] polymers for drug/antigen delivery systems with known adjuvanticity [ 38 44 ]. However, surprisingly, it has limited exploration for Shigella vaccine development wherein only a handful of studies involving nanoparticulate-delivery systems have been reported [ 45 48 ]. Size of such polymeric systems can also significantly affect cellular uptake and immune cell activation.…”
Section: Introductionmentioning
confidence: 99%